2001
DOI: 10.1074/jbc.m102722200
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interaction and Not Glycosylation Determines the Binding Selectivity of Heterodimers between the Calcitonin Receptor-like Receptor and the Receptor Activity-modifying Proteins

Abstract: The receptor activity-modifying proteins (RAMPs) and the calcitonin receptor-like receptor (CRLR) are both required to generate adrenomedullin (AM) and calcitonin gene-related peptide (CGRP) receptors. A mature, fully glycosylated, form of CRLR was associated with 125 I-CGRP binding, upon co-expression of RAMP1 and CRLR. In contrast, RAMP2 and -3 promoted the expression of smaller, core-glycosylated, CRLR forms, which were linked to AM receptor pharmacology. Since core glycosylation is classically a trademark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 19 publications
6
94
1
1
Order By: Relevance
“…This discrepancy could be due in part to interference by the extra N-terminal tyrosine residue (Tyr 0 ). In any event, the contribution of the RAMP1 C-tail to CGRP potency is much smaller than that made by its extracellular domain (13,17,32,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be due in part to interference by the extra N-terminal tyrosine residue (Tyr 0 ). In any event, the contribution of the RAMP1 C-tail to CGRP potency is much smaller than that made by its extracellular domain (13,17,32,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…When RAMP chimeras were co-transfected into cells together with CRLR, their binding characteristics and functionality revealed that the determinants of CGRP and AM selectivity reside in the extracellular domains of RAMP. Moreover, Hilairet et al (11) showed that when complexed with CRLR, RAMPs are situated close to the agonist binding pocket because ificity by contributing to the structure of the ligand-binding pocket or by allosteric modulation of the conformation of the receptor. Consistent with that idea, we recently used various RAMP chimeras and deletion mutants to show that a sevenresidue segment situated between the residues (Trp-Cys and Tyr) in hRAMP2 (amino acids 86 -92) and hRAMP3 (amino acids 59 -65) is essential for high affinity agonist binding to hAM receptors but not for the interaction of RAMP with CRLR (12).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of RAMPs, various RAMP chimeras have been used to investigate the structural determinants of CGRP and AM receptor specificity (8,11,12,27). When RAMP chimeras were co-transfected into cells together with CRLR, their binding characteristics and functionality revealed that the determinants of CGRP and AM selectivity reside in the extracellular domains of RAMP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations